PENGARUH DIGITAL MARKETING TERHADAP PENJUALAN INDIHOME (STUDI PADA PT. TELEKOMUNIKASI INDONESIA DI DAERAH BSD TANGERANG SELATAN) - Gina Emily Napitupulu; Remista Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
This study aims to describe and analyze the influence of digital marketing on Indihome sales in the BSD South Tangerang area. This study uses a questionnaire via google form as a research instrument. Data processing using SPSS v25 software uses the correlation coefficient test, t test, coefficient of determination, and simple linear regression. The correlation coefficient test r count is 0.366, which means that sales have a not strong relationship with digital marketing. The t-test results show that digital marketing has a significant effect on sales as evidenced by the t-count value of 3.453 > t-table 1.990 and the digital marketing variable is indicated by a determination test of 13.4%, which means it has a negative effect on sales while the rest is influenced by other factors outside of this research. Simple linear regression shows Y= = 26,376 + 0.244X as a formula, which means that if digital marketing has no sales then consumers are at 26,376 and if digital marketing increases by 1 unit then sales increase by 0.244 units. It can be seen that digital marketing has a significant effect on sales.